Pemetaan Kawasan, Komposisi dan Struktur Mangrove Sebagai Dasar Pengelolaan Suberdaya Ikan di Teluk Cempi, Sumbawa - Nastiti, Adriani Sri; Ridwan, Muhamad; P. Utaminingrum, Hetty Irawati; Putri, Masayu Rahmia Anwar (Perhimpunan Biologi Indonesia, 2015)
Scientific information about the composistionand structures of mangrove community and zonation patterns, became a basic data to support further fisheries research and development. As one of the reference for Dompu government policy on the fisheries recovery plan in Cempi bay data and information of mangrove in this area were very important. The study was conducted at Cempi bayon the year 2011-2012 by exploration the area nearby research station. The results showed that the mangrove forest has already been heavy disturbed and degraded. The mangrove forest at Mbawi only which has a high density andÃÂ good crown coverage. The mangrove species grown in these areas were belonging to the family Rhizophoraceae and Aviciniaceae. The presences of mangrove spesies were supported by environmental factors, such as muddy sandysubstrats and extreme deferences of salinity (3-36o/oo). Recovery of mangrove forest was important to be conducted in order to support the catch shrimp productivity in bay of Cempi.ÃÂ Key Words : Mapping, Composition,ÃÂ Mangrove, Management of Fish Resources, Cempi GulfÃÂ